2021
DOI: 10.1039/d1tc01831k
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric Ln(HCO2)(C2O4) frameworks: synthesis, structure and magnetic properties

Abstract: This study probes the structure and the magnetic properties of members of the Ln(HCO2)(C2O4) (Ln = Sm3+-Er3+) family of coordination frameworks. These frameworks adopt a Pnma orthorhombic structure with one-dimensional...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The structure of the Ln 3 (adipate) 4.5 (DMF) 2 series suggests that the dominant magnetic coupling is likely to occur within the edge-sharing chains, which are likely ferromagnetic for Er 3 (adipate) 4.5 (DMF) 2 . It has been shown that the MCE of frameworks can be optimized for lower fields and higher temperatures through the inclusion of ferromagnetic chains, although if this is the case here for Er 3 (adipate) 4.5 (DMF) 2 , as indicated above, it would be the first time that ferromagnetic chains in an Er material lead to an optimization of its MCE in this way. ,, Although the overall performance is modest, this suggests that Er-containing phases should not be neglected in the search for magnetocalorics optimized for use under low applied fields. Although beyond the scope of this study, the presence of anisotropic thermal expansion within this framework series may suggest another method of tuning the magnetic properties at low temperature, even if the change in unit cell dimensions with the temperature at which these materials are useful magnetocalorics might be quite small.…”
Section: Resultsmentioning
confidence: 88%
“…The structure of the Ln 3 (adipate) 4.5 (DMF) 2 series suggests that the dominant magnetic coupling is likely to occur within the edge-sharing chains, which are likely ferromagnetic for Er 3 (adipate) 4.5 (DMF) 2 . It has been shown that the MCE of frameworks can be optimized for lower fields and higher temperatures through the inclusion of ferromagnetic chains, although if this is the case here for Er 3 (adipate) 4.5 (DMF) 2 , as indicated above, it would be the first time that ferromagnetic chains in an Er material lead to an optimization of its MCE in this way. ,, Although the overall performance is modest, this suggests that Er-containing phases should not be neglected in the search for magnetocalorics optimized for use under low applied fields. Although beyond the scope of this study, the presence of anisotropic thermal expansion within this framework series may suggest another method of tuning the magnetic properties at low temperature, even if the change in unit cell dimensions with the temperature at which these materials are useful magnetocalorics might be quite small.…”
Section: Resultsmentioning
confidence: 88%
“…Single-molecule magnet (SMM) and magnetocaloric effect (MCE), inter alia , are the two most important lanthanide-magnetism topics that have tantalized the attention of both chemists and physicists in recent years. The Dy 3+ compounds, because of their significant anisotropy arising from large unquenched orbital angular momentum and a high energy reversal barrier, more-often-than-not show slow magnetic relaxation and dominate SMM studies. On the other hand, the Gd 3+ ion, by virtue of its large spin-only magnetic moment, weak superexchange interaction, and quenched orbital momentum, predominates the recent quest for low-cost, environmentally benign cryogenic technology using MCE-based magnetic refrigeration. Notwithstanding their individual magnetic features, the combination of Dy 3+ and Gd 3+ with transition metals is often found to excel the magnetic behavior. …”
Section: Introductionmentioning
confidence: 99%
“…Since the diamagnetic ligands involved in molecules will reduce the magnetic density, the experimental Δ S m values they got are usually smaller than the theoretical ones. Considering increasing the magnetic density or reducing the M w / N Gd ratio, one approach is to use light organic ligands such as HCOO − and C 2 O 4 2− which can decrease the molecular weight; 25,32,33 another effective strategy is to construct a highly dense cluster-based metal–organic framework (MOF) material. 4,6,9,24,34–39…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] Obviously, the larger the amount of Gd III atoms in the molecule, the larger the value of nR ln(2S + 1) will be obtained. To date, some high-nuclearity Gd-based molecular magnetic cooling materials with large theoretical ΔS m values such as {Gd 48 }, 28 {Gd 60 }, 29 {Gd 104 } 30 which can decrease the molecular weight; 25,32,33 another effective strategy is to construct a highly dense cluster-based metal-organic framework (MOF) material. 4,6,9,24,[34][35][36][37][38][39] Moreover, iminodiacetic acid (H 2 IDA) has been demonstrated to be a favorable ligand, which can coordinate with metal ions to form 0D high-nuclearity Gd-based clusters with a good magnetocaloric effect (MCE), but few of them are cluster-based MOFs.…”
Section: Introductionmentioning
confidence: 99%